INTEGRATING INCLUSIVE DESIGN' AWARENESS INTO ARCHITECTURE EDUCATION - Ergenoglu, A. Sungur; Bayraktaroglu, B. (IATED-INT ASSOC TECHNOLOGY EDUCATION A& DEVELOPMENT, 2016)
Together with the introduction of 'universal design', 'inclusive design' and related concepts, the aim and the target for 'accessibility' have taken a new direction, and a totally new understanding through these concepts has developed. It has been widely recognised that; not only being 'accessible' and being compatible with the standards are enough, but also looking from perspective of 'fundamental human rights'; 'inclusivity' is essential. As 'universal' and/or 'inclusive' design requires further than the standards, the importance of social, psychological and aesthetic dimensions of accessibility is now a rising trend in the area of design. And for these dimensions to be seeked by the society, a certain point of awareness has to be reached beforehand. It is a well-known fact that education forms the foundation of 'accessibility awareness' in the society. As for the architectural arena, architects, who are sensitive and willing to take action are required, to move on to the next level that is namely; 'inclusivity'. In order for the professionals to be fully aware of this particular subject, integrating accessibility into design education is vital. Therefore, the first objective of this paper is to determine the awareness levels of architecture students. Although, the awareness levels of architecture students are not always easy to determine, as everyone seems to agree in the matter of designing accessible spaces, yet, the results in everyday life are not sufficient and not pointing out to an inclusive environment. Even though the education covers the topic, inclusivity is not present in new designs and projects, much as it ought to be. In the paper, the reasons why the knowledge and awareness about inclusive design that are taught in universites are not being reflected to our environments are searched afterwards. The answers are thought to meet a very important need by means of determining the problem and moving on with the right strategy. With this aim, a case study is conducted. A questionnaire form about inclusivity, of which the answers could not be predicted without right judgement skills is applied to the subjects. In the paper, the results of a case study with the aim to determine the awareness levels of architecture students are presented. The study was conducted with the undergraduate architecture students of 3 universities in Istanbul. The selection of the universities was based on the presence of theoretical courses directly focusing on the issues of 'inclusivity' and 'accessibility'. The results of the case study are given in the paper in detail, which lead to a discussion of the effects of the theoretical courses about accessibility. Also another discussion about 'being aware' and 'being competent' in the design phase and the practical area is introduced. The paper also offers some suggestions to enhance the awareness and the qualification of architecture students in these issues, as the authors are also conducting 'design studios' and observing the weak aspects concerning inclusivity issues.
Keywords: Inclusive design; architectural education; universal design; inclusive design education; accessibility; architecture schools; Education & Educational Research